Efficient, High-Yield Purification of Pulegone from the Oriental Herb, Schizonepeta tenuifolia Briquet and Demonstration of Supramolecule Formation by Cyclodextrins - Cho, Hyun-Jung; Yoo, Dong-Chan; Kim, Hee-Joon; Khang, Kong-Won; Jeong, Ho-Soon; Yang, Seun-Ah; Lee, In-Seon; Jhee, Kwang-Hwan (Asian Journal of Chemistry, 2010)
Pulegone is an organic compound obtained from the essential oils of a variety of plants. Biomaterial screening of various herbs has demonstrated that large amounts of pulegone are present in Schizonepeta tenuifolia Briquet. To purify this useful volatile compound for nanobiomaterials, we prepared extracts from 220 g of Schizonepeta tenuifolia Briquet with chloroform at 55 ºC for 12 h and concentrated the extracts under reduced pressure. We obtained a total of 9.48 g, which was then solubilized with hexane and subjected to silica gel column chromatography and eluted with hexane/chloroform solvents. The resulting pulegone was more than 99 % pure, based on estimates using multiple spectroscopic analyses, including APCI-MS, gas chromatography, GC-MS and UV-visible absorbance. Supramolecule encapsulation of purified pulegone with cyclodextrins was shown by the fluorescence spectrum. These supramolecules have the ability to permeate hydrophilic biological membranes and might offer important advantages in various applications for cosmetic, pharmaceutical and food-flavour industries.